FAKTOR KEPRIBADIAN DAN ORGANIZATIONAL CITIZENSHIP BEHAVIORPADA POLISI PARIWISATA - Suseno, Miftahun Ni’mah (Universitas Ahmad Dahlan, 2012)
AbstractThe aim of this research was to understand relationship betweenOrganizational Citizenship Behavior and Personality Factor. The subjects of this research are members of tourism police in Yogyakarta, total subject are 54 people. Data collected with two scales consist of Organizational Citizenship Behavior Scale and Big Five Personality Scale. Data was analyzed with correlation product moment. The result showed there is no correlation between neuroticism and Organizational Citizenship Behavior,there is positive correlation between extraversion and Organizational. Citizenship Behavior, there is no correlation between opennes to experience and Organizational Citizenship Behavior, there is positive correlation between agreeableness and Organizational Citizenship Behavior, and there is positive correlation between conscientiousness and OrganizationalCitizenship Behavior.Keywords: organizational citizenship bhavior, personality factor, police tourism,